Sensitization to Aeroallergens in Patients with Respiratory Allergies Based on Skin-Prick Test Results - G Bejtullahu; N Karahoda; H Pupovci; V Lokaj-Berisha; N Berisha; B Lumezi; L Ahmetaj (Tehran University of Medical Sciences, 2012)
Background: The aim of this study was to identify the most common aeroallergens in patients with asthma and rhinitis.Methods: The study enrolled 102 participants including 64 patients with respiratory allergies (among them 15 were clinically diagnosed as asthma patients, 41 with rhinitis, 8 were both) and 38 healthy controls. All of participants were subject of skin prick tests (SPT) with series of common allergenic extracts. Sera from all participants were tested for total IgE and eosinophil count. To measure airflow limitation and reversibility in asthma patients the pulmonary function testing were carried out.Results: M/F ratio was 1:1.6 in patients and 1:0.7 in control group with mean age 28.88 year (SD 13.16; range 6 - 55year) and 20.47 respectively (SD 1.16; range 19-23 year). The most common risk factors in these patients were total IgE more than 100 IU/ml, eosinophils above 4% and positive family history of atopy. Skin prick testing results showed prevalence rates for allergen groups in this manner: house dust mites 81.3 %, pollens 57.8 %, animal dandruff12.5% and moulds 4.9%. Polysensitization was common in 51.6% of all sensitized patients being positive to more than one group of allergens.Conclusion: House dust mites are the main sensitizing allergens among our allergic patients as well as healthy controls. Next in importance, in all participants, are grasses. This pattern of prevalence was expected based on herbal geography, climate and specially lifestyle. It was also compatible with the results from studies carried out in places with the same habitat.